ANALISIS PAJAK, TUNNELING INCENTIVE, DAN MEKANISME BONUS TERHADAP TRANSFER PRICING PADA PERUSAHAAN SEMEN YANG TERDAFTA DI BURSA EFEK INDONESIA - Baviga, Rio; Desiyanti, Rika (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aimed to determine the influence of : (1) Tax (2) Tunneling Incentive And (3) Mechanism Fee on Transfer pricing to cement companies listed on Indonesia. The research period was 2017-2021. This research was classiefed as ex post facto research, causal associative, and quantitative approach. This population in this study was all cement companies listed in Indonesia stock exchange (IDX) in 2017-2021. the research sample technique used purposive sampling technique. Data analysis method used multiple linear regression. The result of the research showed that : The tax hat no effect to Transfer pricing with regression confficient 0,059 and significance 0.588. Tunneling Insentive had positive effect to Transfer pricing with regression coefficient 1,344 and significance 0.273. Mecanism Fee effect to Transfer pricing with regression confficient -0,791 and significance 0,000. The Tax, Tunneling Insentive and Mecanism Fee, effect the Transfer pricing of cement companies listed in indonesia stock exchange (IDX) in 2017-2021 with F-count 3,413 and significance 0,000. The result of the adjusted R2 test in this study obtained a value of 0.818. This showed that the Transfer pricing was influenced by The Tax, Tunneling Insentive, and Mecanism Fee of 81,8 %, while the rest of 18,2% was influenced by other factors not examined in this study